Relationship between CYP2B6*6 and cold pressor pain sensitivity in opioid dependent patients on methadone maintenance therapy (MMT) - Zahari, Z.; Lee, C.S.; Ibrahim, M.A.; Musa, N.; Mohd Yasin, M.A.; Lee, Y.Y.; Tan, S.C.; Mohamad, N.; Ismail, R. (Elsevier, 2016)
Background